BIOACTIVE COMPOUNDS IN MEDICINAL PLANTS AS A SOURCE OF ANTI-PARASITIC: REVIEW ARTICLE - Al-Quraghuli, Abdullah Zaidan Khalaf; Ali, Jassim Mohammed (PT. Antis International Publisher, 2025)
Objective: Despite the considerable worldwide health and economic burden imposed by gastrointestinal parasites in humans and cattle, treatment alternatives are increasingly hindered by multidrug resistance and the detrimental effects of synthetic medications. Method: This review encapsulates the antiparasitic potential of medicinal plants and their phytochemicals, elucidates their modes of action and pharmacological relevance, and examines their position as a possible source for next-generation antiparasitic therapeutics. Results: Medicinal plants, abundant in structurally varied bioactive chemicals including flavonoids, alkaloids, terpenoids, tannins, and essential oils, have historically served as significant sources of medicinal medicines. Novelty: This review encapsulates the antiparasitic potential of medicinal plants and their phytochemicals, elucidates their modes of action and pharmacological relevance, and examines their position as a possible source for next-generation antiparasitic therapeutics.